Kepuasan Kerja Pada Karyawan Toko Grosir Artha - Nova Laura Putri Marbun; Nurlita Octaviani; Santi Pertiwi Hari Sandi; Dwi Epty Hidayaty (Madani: Jurnal Ilmiah Multidisiplin, 2023)
Aims to identify and analyze the factors that influence employee job satisfaction at Artha stores. Through data collection through observation, surveys, interviews. So it succeeded in identifying that employee performance, work motivation, work environment have a positive influence on job satisfaction. To increase employee job satisfaction, companies need to pay attention to several factors. it is important for companies to pay attention to the work culture that is in it. A positive and inclusive work culture can create a supportive and motivating environment for employees. Good leadership also plays an important role in increasing job satisfaction. Leaders need to motivate employees by giving recognition and appreciation for the work done. In addition, they also need to ensure that employees have sufficient resources to complete their tasks properly. By paying attention to these factors, companies can create a better work environment, increase employee motivation, and ultimately increase their job satisfaction. This will have a positive impact on employee performance and overall company success.